Patricia Crone’s Critical Notes On The Chronological Discourse On The Al-Qur’an In Macca - Al Amirul Fitriana Dewi; Inayah Rohmaniyah (Institut Agama Islam Sumatera Barat, 2023)
This article will reveal the epistemological basis of Patricia Crone's view that Mecca is not a center for international trade and a place for the distribution of the Koran. This study is qualitative research that uses document data sources or what is also called library research. The results of the research by Patricia Crone indicate 3 different aspects in studying the originality of the chronology of the decline of the Al-Qur'an. First, in a skeptical manner, Crone suggests that the chronology of the revelation of the Koran is more appropriate to pin it down in Iraq rather than in Mecca. Second, his thoughts were obtained from non-Muslim sources which ultimately outlined contradictory thoughts which were inversely proportional to the Makkiyah and Madaniyah Qur'an surah groups. Third, the social situation when the Koran was revealed was not in a primitive society, as is generally described in the Traditionalist school of thought, but in a society that was more advanced, more philosophical and sophisticated. This research requires refinement and is expected to provide new insights in future research.